The Survival Force of Literature - Kowalska-Nadolna , Urszula (Poznańskie Studia Slawistyczne, 2020)
The following review article brings a presentation of the published in 2018 encyclopaedia of Czech literary samizdat. The analysed publication consists of two parts – a comprehensive introduction discussing the question of independent literary culture in Czechoslovakia under communist regime pressure and an entry section with more than 300 entries about Czech independent self-publishing activities. The presentation of the following book provokes the need to re-examine the phenomenon of Czech samizdat, reflecting on its chronological framework, definition, meaning and role in creating and keeping alive an independent culture in the era of domination of the communist regime (1948–1989).